Innovative Transformation Geometry Learning: Developing Augmented Reality Media to Boost Students' Critical Thinking - Meke, Konstantinus Denny Pareira; Seto, Stefania Baptis; Tupen, Stefanus Notan (Insitut Agama Islam Negeri Kerinci, 2025)
This study aims to develop an Augmented Reality (AR)-based transformation geometry learning media to enhance students' understanding and critical thinking skills. The method used is Research and Development (RnD) with a waterfall software development model. This model is chosen due to its systematic and sequential nature, which facilitates the clear mapping of each development stage. The development stages include planning, design, construction, testing, and implementation, involving validity testing by experts and product trials with students. The validity results show that the developed AR application is deemed highly feasible by media and subject matter experts, with validity percentages reaching 82% and 83%, respectively. Product trials with students showed that the AR application is practical to use, with a student learning completion rate of 88.4%. The results of this study indicate that AR-based learning media is effective in improving students' understanding of transformation geometry concepts and enhancing their critical thinking skills. The implication of this research is that AR-based learning media can be integrated into mathematics teaching, particularly for geometry topics, to improve teaching effectiveness and foster the development of better critical thinking skills in students.